Educational outcomes of agriculture education on students in U.S. urban schools, a review of current literature - Bell, Kaleb (My University, 2026)
This report examines the historical foundations and contemporary realities of urban agricultural education in the United States. Drawing on 42 scholarly and historical sources, Chapter one situates agricultural education along a continuum spanning Indigenous knowledge systems, the institutionalization of land-grant universities, and the emergence of modern Urban Agriculture (UA) initiatives. The review highlights how experiential learning has shaped agricultural knowledge transmission from Indigenous practices to Deweyan philosophy. While agricultural education has expanded through extension, national organizations, and federal funding initiatives, systemic barriers have historically limited access for BIPOC and urban populations. Contemporary programs seek to address these inequities by promoting food security, civic engagement, and student well-being. Grounded in Social Cognitive Theory and Self-determination Theory, this review argues that hands-on curricula are central to engaging and retaining urban youth within agricultural pathways.   Building on these findings, the second and third chapters document the development of a four-week, adaptable curriculum designed for use in middle-grade classrooms. This curriculum translates experiential and systems-based principles into structured lessons that emphasize career exploration, horticultural and animal science literacy, food systems analysis, and cross-curricular integration with math and science. Using the Backwards Design process, the curriculum was created through iterative cycles of planning, classroom implementation, student feedback, and revision. The curriculum serves as a testing ground for the theoretical claims advanced in chapter one. Together, the literature review and curriculum development process demonstrate that agricultural education can function as a rigorous and culturally responsive framework capable of strengthening academic skills while reconnecting urban students to the systems that sustain their lives.
Keywords: Agriculture education; Urban agriculture; Student outcomes; Secondary school